Collaborative Leadership Strategies to Prevent Crabs in A Barrel Syndrome in Early Childhood Education Institutions - Suteki, Mega; Sulistyowati, Retno Wuri; Harmawati, Diah; Wahyudin, Wahyudin; Along, Antonius (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
The "Crabs in a Barrel Syndrome" (CBS), a behaviour characterised by undermining peers to maintain one’s own position, can hinder collaboration and innovation in Early Childhood Education (ECE) institutions. This study aims to examine how CBS manifests in the workplace culture of ECE teachers and to explore collaborative leadership strategies to mitigate such behaviours. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and documentation involving 9 participants across three ECE centres in Merauke, Indonesia. Thematic analysis was conducted using Braun and Clarke’s six-step framework. The findings reveal that CBS manifests as fear of dominance, resistance to change, and avoidance of open collaboration. However, interventions such as weekly reflection forums, collective appreciation systems, and participatory leadership proved effective in fostering trust, enhancing team cohesion, and nurturing a more constructive work environment. This study concludes that organisational designs that promote psychological safety and transparent communication are essential in countering harmful competitive cultures. Theoretically, the research contributes to the understanding of micro-organisational dynamics in educational settings, while practically, it offers concrete recommendations for ECE administrators to cultivate inclusive and collaborative workplaces.